2004
DOI: 10.4315/0362-028x-67.11.2603
|View full text |Cite
|
Sign up to set email alerts
|

Colicin Concentrations Inhibit Growth of Escherichia coli O157:H7 In Vitro

Abstract: Escherichia coli O157:H7 is a virulent foodborne pathogen that causes severe human illness and inhabits the intestinal tract of food animals. Colicins are antimicrobial proteins produced by E. coli strains that inhibit or kill other E. coli. In the present study, the efficacy of three pore-forming colicins (E1, N, and A) were quantified in vitro against E. coli O157:H7 strains 86-24 and 933. Colicins E1 and N reduced the growth of E. coli O157:H7 strains, but the efficacy of each colicin varied among strains. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 24 publications
1
15
0
1
Order By: Relevance
“…Thus, directly inoculated pathogens in wastewater declined rapidly, with a decimal reduction time of 3.5 days, while they persisted inside 300-kDa dialysis tubes (decimal reduction time of 18.5 days). Yet the significant decline in pathogen numbers in 1-kDa tubes compared to that in the high-molecular-weight-cutoff tube is unexpected, although the pathogen may also be protected from colicins (8) and antibiotics produced from native organisms in wastewater. Exclusion of nutrients and growth factors of Ͼ1 kDa is hypothesized for the pathogen decline inside the low-molecular-weight-cutoff dialysis tube.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, directly inoculated pathogens in wastewater declined rapidly, with a decimal reduction time of 3.5 days, while they persisted inside 300-kDa dialysis tubes (decimal reduction time of 18.5 days). Yet the significant decline in pathogen numbers in 1-kDa tubes compared to that in the high-molecular-weight-cutoff tube is unexpected, although the pathogen may also be protected from colicins (8) and antibiotics produced from native organisms in wastewater. Exclusion of nutrients and growth factors of Ͼ1 kDa is hypothesized for the pathogen decline inside the low-molecular-weight-cutoff dialysis tube.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, feeding cattle with a straw-rich diet (12), silage made with bacteriocin-producing bacteria (3), and competitive exclusion products using lactic acid bacteria (7), colicinogenic E. coli (8,33) and O157-specific bacteriophages (35) has the potential to inhibit pathogen replication inside the animals. Nevertheless, releasing even a few cells into environments that favor pathogen regrowth (10) may pose an epidemiological risk.…”
mentioning
confidence: 99%
“…Supershedders are cattle that excrete the pathogen at concentrations of Ն10 4 CFU · g Ϫ1 of feces (5); they are thought to account for a small proportion of the cattle population and yet may contribute 80 to 96% of the total load of E. coli O157:H7 in the herd (5)(6)(7). Multiple factors contribute to shedding of E. coli O157:H7 in cattle, including diet (8), housing (9), season (10), stress (11), and age (12). However, knowledge of the microbial ecology of the gastrointestinal tract of cattle is limited, and relationships among microbiota may impact the ability of E. coli O157:H7 to persist in some cattle (13).…”
mentioning
confidence: 99%
“…has allowed colicins to be produced in greater amounts from different recombinant host systems so that proof-of-concept studies could be performed (17)(18)(19). These studies demonstrated that colicins could be used to reduce populations of several species of foodborne pathogenic bacteria on food products, and in live animals (20).…”
Section: Colicins a Smart Arrowmentioning
confidence: 99%